Synthesis of 1-azabicyclo[3.2.2]nonane from cinchonidine - Mujahidin, Didin; Hoffman, Hans Martin Rudolf (Research Institute for Tea and Cinchona, 2013)
The 1-azabicyclo[3.2.2]nonane is a potent building block which have important bioÂlogicaly activities including for Alzheimer and ashmatic treatment. The skeleton can be accessed by rearrangement of quinuclidine ring in Cinchona alkaloids. The rearrangeÂment established three chiral center at C-2, C-3, and C-6. The rearrangement of quiÂnuclidine moiety to azabicyclic[3.2.2]nonana system of mesylated cinchonidine took place by hydrolysis in a mixture of acetoneâwater (1:1) with 47% yields. The structure determination of the product and its absolute configuration of chiral centers were estaÂblished by using spectroscopy data including, 1H NMR, 13C NMR, 1D NOE and HR-MS.